Bottlebrush Elastomers: A New Platform for Freestanding Electroactuation. Issue 2 (8th November 2016) - Vatankhah‐Varnoosfaderani, Mohammad; Daniel, William F. M.; Zhushma, Alexandr P.; Li, Qiaoxi; Morgan, Benjamin J.; Matyjaszewski, Krzysztof; Armstrong, Daniel P.; Spontak, Richard J.; Dobrynin, Andrey V.; Sheiko, Sergei S.
Abstract : Freestanding, single‐component dielectric actuators are designed based on bottlebrush elastomers that enable giant reversible strokes at relatively low electric fields and altogether avoid preactuation mechanical manipulation. This materials design platform allows for independent tuning of actuator rigidity and elasticity over broad ranges without changing chemical composition, which opens new opportunities in soft‐matter robotics.